Kepemimpinan Kepala Sekolah dan Manajemen Organisasi di SD Juara Batam - Juniar Sinaga; Suyud Suyud; La Musa (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The aim of this research is to describe the Leadership and Organizational Management model at Juara Elementary School Batam, Kepulauan Riau. The research method used is qualitative descriptive. Data collection techniques involved observation through interviews. The interviews included questions related to aspects of leadership and management, covering the presence of the school principal, effectiveness of communication, leadership involvement, ability to motivate and inspire, skills in guiding, and demonstration of work ethics and integrity. The data analysis technique comprised data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that school leadership at Juara Elementary School Batam significantly influences teacher motivation, organizational culture, management, learning organization, and school effectiveness. The school leaders at Juara Elementary School Batam assume various effective leadership roles, such as guiding the organizational team, motivating and energizing organizational members, creating a positive work environment, and fostering cooperation and collaboration. The principal of Juara Elementary School Batam has contributed to the development of a positive and productive organizational culture through discipline, teamwork, effective communication, motivation, and work-life balance.